PERANAN UKM ANEKA BUAH DALAM PASAR EKSPOR (UKM OLAHAN BUAH KOTA MALANG JAWA TIMUR) - Siti Munfaqiroh; Enggar Nursasi; Uke Prajogo (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2017)
The export products such as fruit chips increasingly demanding public. Malang is known as one of the premier tourist destination in East Java, it's cold many sites of historical sites and many interesting attractions, along with the rapid development of tourism is also developing in the center by the poor with andalanya icon is tempe chips and fruit chips. Science activities for Export Product performed on both partners to produce fruit chips, namely CV Kajeye Food Arjosari Malang and CV Jago Pakis Jaya in Malang aims to provide reinforcement for both partners in the application of technology and improving the quality and quantity of products to be exported. Both partners feel the support that is appropriate to their needs to improve its business mainly in activating the export of products in the form of support equipment frezeer / Coolstorage, Spinner and Vacuum Frying and mentoring to both the UKM partners in order to improve the quality and quantity of the products supplied in the form of training to improve employee productivity through 5 R.